2002
DOI: 10.1046/j.1440-1703.2002.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rainfall events on soil CO2 flux in a cool temperate deciduous broad‐leaved forest

Abstract: The effects of rainfall events on soil CO2 fluxes were examined in a cool temperate Quercus/Betula forest in Japan. The soil CO2 fluxes were measured using an open‐flow gas exchange system with an infrared gas analyzer in the snow‐free season from August 1999 to November 2000. Soil CO2 flux showed no significant diurnal trend on days without rain. In contrast, rainfall events caused a significant increase in soil CO2 flux. To determine the effect of rainfall events and to evaluate more precisely the daily and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 36 publications
11
89
2
2
Order By: Relevance
“…Similar responses have been reported in other trials (Kieft et al 1987;Lee et al 2002;Borken et al 2003;Lee et al 2004), although the factors responsible for the pulse are not fully understood. Displacement of soil air by water can affect the rate of CO 2 efflux from the soil; however Lee et al (2004) demonstrated that this phenomenon accounts merely for 0.4-0.8 µmol CO 2 m -2 s -1 in their study.…”
Section: Response Of Soil Respiration To Simulated Rainfallsupporting
confidence: 77%
“…Similar responses have been reported in other trials (Kieft et al 1987;Lee et al 2002;Borken et al 2003;Lee et al 2004), although the factors responsible for the pulse are not fully understood. Displacement of soil air by water can affect the rate of CO 2 efflux from the soil; however Lee et al (2004) demonstrated that this phenomenon accounts merely for 0.4-0.8 µmol CO 2 m -2 s -1 in their study.…”
Section: Response Of Soil Respiration To Simulated Rainfallsupporting
confidence: 77%
“…Another important variable affecting respiration rates is soil water content. Low CO 2 emissions are often observed when soils are either waterlogged or dry (Ball et al, 1999;Lee et al, 2002;Howard and Howard, 1993;Smith et al, 2003). In 2003 a continuous decrease of soil moisture was observed: from 22% at the end of May to 8% at early September.…”
Section: Co 2 Emissionsmentioning
confidence: 99%
“…These models typically use soil temperature (Fang et al, 1998;Buchmann, 2000;Janssens and Pilegaard, 2003), soil moisture (Davidson et al, 1998;Epron et al, 2004;Sotta et al, 2004) as well as their interaction (Tufekcioglu et al, 2001; Lee et al, 2002;Tang and Baldocchi, 2005) for largescale soil respiration estimates. However, whereas soil temperature and moisture are good predictors of the temporal variation of soil respiration, they are inadequate to explain the spatial variations of soil respiration within a site and between sites (Xu and Qi, 2001;Tang and Baldocchi, 2005).…”
Section: Introductionmentioning
confidence: 99%